Macrophage migration inhibitory factor mediates joint capsule fibrosis via facilitating phospholipid metabolite PGE2 production in fibroblasts - Yuxin Zhang; Xin Jiao; Yijia Wang; Shilu Liu; Zengguang Wang; Hanwen Chang; Yuntao Li; Xiaokun Yue; Xiaoding Gu; Renjie Xu (Cellular and Molecular Life Sciences)
Abstract Background Joint capsule persistent inflammation and subsequent fibrosis lead to post-traumatic joint contracture (PTJC). Fibroblasts, as a bridge between inflammation and fibrosis, participate in regulating the pathological microenvironment after injury. Macrophage migration inhibitory factor (MIF) is a proinflammatory cytokine that can be inducibly expressed in lesioned joint capsule, yet its role in regulating fibroblast function to tune milieu following PTJC remains elusive. Methods The influence of MIF on the expression of phospholipid metabolite prostaglandin E2 (PGE2) and relevant pathways were investigated using qRT-PCR, Western blot, ELISA, EdU, Transwell, siRNA, and immunofluorescence following establishment of rat PTJC model, fibroblast model, and macrophage model. Results MIF/COX2/PGE2 synchronously increased in injured joint capsules following PTJC. Treatment the lesion sites with MIF inhibitor 4-IPP significantly reduced the expression of COX2 and PGE2. In vitro, MIF activated COX2/PGE2 pathway in joint capsule fibroblasts through interaction with membrane receptor CD74 and subsequent regulation of ERK/CREB signaling. Joint capsule fibroblast-derived PGE2 in turn selectively modulated fibroblast and macrophage functions to synergistically promote the inflammation and fibrosis process. Conclusions Our results reveal a novel function of MIF-mediated fibroblast, which tunes pathological microenvironment by activating phospholipid metabolism to accelerate and exacerbate joint capsule inflammation and fibrosis. These suggest a new insights and potential therapeutic strategy for inflammation- and fibrosis-associated diseases.